Fermentation optimization of pediocin PD-1 production and a comparative study of the effect of pediocin PD-1, plantaricin 423 and nisin on biofilms of Oenococcus oeni - Nel, Hannes Augustinus (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2001.